Seagrass Community in the Coastal Waters of Hitalawa Beach, Negeri Oma, Indonesia - Gilvano Siahaya; Frijona Fabiola Lokollo; Imanuel Villian Trayanta Soukotta; Frederick Rijoly; Krisye Pasanea (Nekton, 2026)
The limited data and information on seagrass ecosystems in Negeri Oma provided the basis for this study. The lack of previous studies offers an opportunity to examine the ecological potential of seagrass more comprehensively and to contribute to the conservation and sustainable management of coastal resources. This study aimed to analyze the species composition and description of seagrass, density and relative density, as well as frequency of occurrence and relative frequency of seagrass species in the coastal waters of Hitalawa Beach, Negeri Oma. The study employed a line transect–quadrat method, consisting of six transects with a total of 30 quadrats. Six seagrass species were recorded, namely Cymodocea rotundata, Halodule pinifolia, Syringodium isoetifolium, Enhalus acoroides, Halophila ovalis, and Thalassia hemprichii. The overall seagrass density reached 89.55 shoots/m², placing the seagrass condition at Hitalawa Beach in scale category 3, namely moderately dense, with a density range of 75–125 shoots/m². The highest frequency of occurrence was recorded for T. hemprichii, which was found in most of the observation plots. Water temperature and salinity across the six transects ranged from 31.2–32.5°C and 27.7–31‰, respectively. The findings indicate that the coastal waters of Hitalawa Beach support a relatively diverse seagrass community with moderately dense seagrass conditions. This study provides updated baseline information on the condition of seagrass beds in the area and may support future coastal resource conservation and management efforts.